The policy of the Kingdom of Saudi Arabia towards political developments in Iraq 1932-1958 - Saeed, Tariq Hassan (Al-Adab Journal, 2015)
The Saudi attitudes towards the independence of the Arab Gulf countries was characterized by the infinite assistance both politically and financially in all international meetings, besides the housing of the politics of the Arabian Gulf on the Saudi land, ease their tasks, assist them distinctly. The Saudi attitudes towards the independence of the Arab Gulf countries also characterized in the United Nations and the Arab affected positively towards reaching to the goal of independence, as in Bahraini’s case when they requested the independence, Iran was considering Bahrain as a part of it, also when Iraq requested the join of Kuwait, the Saudi Arabia refused that. The other attitudes were with Qatar, United Arab Emirates and Oman to get their independence and getting a seat in League and the United Nations. All of these attitudes, reflected on and changed the future of these countries.